Pengaruh Moralitas Individu, Budaya Organisasi, Dan Sistem Pengendalian Internal Terhadap Risiko Fraud - Cahyaningrum, Regita Putri; Muslimin, Muslimin; Sunani, Avi (Jambura Economic Education Journal, 2025)
The aim of the following research is to understand the influence of individual morality, organizational culture, and the internal control system on the risk of fraud in the management of the APBDes in Buduran District. The method used is quantitative. Research results show that individual morality has a significant impact on the risk of fraud. Organizational culture does not have a significant impact on fraud risk and the internal control system does not have a significant impact on fraud risk. The conclusions from this research are as follows: (1) a high level of individual moral reasoning does not rule out the possibility that someone will commit fraud, especially in terms of APBDes management; (2) a bad culture does not guarantee that fraud does not occur, organizational culture cannot reduce fraud caused by intimidation and dishonesty of village officials who encourage agencies to achieve certain goals related to village financial fraud; (3) the village government does not implement an internal control system well, which shows a low level of internal knowledge